ANALYSIS OF LEGAL POLICY IMPLEMENTATION AGAINST PERPETRATORS OF CHILD BULLYING - Sulistina, Sulistina; Sari, Amilia Putri Kartika; Yusri, Efrilia; Musdalifah, Arindy Sri (Universitas Nurul Jadid, 2025)
Bullying is a common occurrence in Indonesia. Many cases of bullying occur in schools, from elementary to secondary education, and even at the university level. The law has its own perspective on children who become perpetrators of crimes. Legal treatment for children in conflict emphasizes the best protection for children, not just retaliation. The method used in this study is normative juridical or normative legal research, also commonly referred to as doctrinal legal research. The discussion in this study will outline the rules and implementation of legal policies against perpetrators of bullying who are minors. The conclusion of this study is that bullying in school-age children is deviant behavior, both in the form of physical and psychological violence, namely by underage children as subjects against other children as objects of the deviation, carried out through physical, verbal, relational, and electronic bullying. Law enforcement against minors who commit bullying refers to Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Legal protection measures for crimes committed by children are pursued. Diversion, however, does not prevent the possibility of criminal sanctions as stipulated in Article 76C of the Child Protection Law.